Association of abnormal serum potassium levels with arrhythmias and cardiovascular mortality: a systematic review and meta-analysis of observational studies - Hoppe, Liesa Katharina; Laetsch, Dana Clarissa; Brenner, Hermann; Schöttker, Ben (Cardiovascular drugs and therapy, 2018)
Purpose: To provide the first systematic review and meta-analysis of observational studies on the association of abnormal serum potassium and cardiovascular outcomes.Methods: Medline and ISI Web of Knowledge were systematically searched from inception until November 24, 2017. Data synthesis of relevant studies was performed using random effects model meta-analyses.Results: Meta-analyses included 310,825 participants from 24 studies. In the older general population, low serum potassium was associated with a 1.6-fold increased risk of supraventricular arrhythmias (risk ratio [95% confidence interval] 1.62 [1.02-2.55]). Contrarily, high serum potassium was associated with increased cardiovascular mortality (CVM) (1.38 [1.14-1.66]). In patients with acute myocardial infarction, the risk of ventricular arrhythmias was increased for high serum potassium (2.33 [1.60-3.38]). A U-shaped association was observed with a composite cardiovascular outcome in hypertensive patients (2.6-fold increased risk with hypokalemia and 1.7-fold increased risk with hyperkalemia), with CVM in dialysis patients (1.1-fold increased risk with hypokalemia and 1.4-fold increased risk with hyperkalemia) and with CVM in heart failure patients (albeit not statistically significant). Further, only hyperkalemia was associated with an increased risk of a composite cardiovascular outcome in both dialysis (1.12 [1.03-1.23]) and chronic kidney disease (1.34 [1.06-1.71]) patients.Conclusions: Controlled clinical trials are needed to determine which populations may profit from more frequent potassium-monitoring and subsequent interventions, e.g., change or withdrawal of potassium-influencing drugs, in order to restore normal values and prevent cardiovascular outcomes.
First online: 20 April 2018
Gesehen am 27.06.2018